2005
DOI: 10.1161/01.str.0000177874.29849.f0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Levels and Five-Year Survival After First-Ever Ischemic Stroke

Abstract: Background and Purpose-This study aimed to investigate the association between plasma adiponectin levels and 5-year survival after first-ever ischemic stroke. Methods-Plasma adiponectin measured within 24 hours after first-ever ischemic stroke was related to 5-year outcome.The Kaplan-Meier technique was applied in survival analysis, and the Cox proportional hazards model was used to evaluate the relationship between risk factors and prognosis. Results-The probabilities of death were 92.8%, 52.5%, and 10.5% (PϽ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 32 publications
4
97
0
5
Order By: Relevance
“…14 Conflicting results have also been published for adiponectin and stroke. Whereas adiponectin levels showed an inverse relation with stroke severity on admission and 5-year survival in a clinic-based study, 15 no association was found between adiponectin and first-time stroke using data from population-based surveys in northern Sweden. 16 Adiponectin levels are considerably higher in women than in men.…”
Section: Introductionmentioning
confidence: 75%
“…14 Conflicting results have also been published for adiponectin and stroke. Whereas adiponectin levels showed an inverse relation with stroke severity on admission and 5-year survival in a clinic-based study, 15 no association was found between adiponectin and first-time stroke using data from population-based surveys in northern Sweden. 16 Adiponectin levels are considerably higher in women than in men.…”
Section: Introductionmentioning
confidence: 75%
“…14 Furthermore, did not predict the development of first ever stroke, 20 but was related to survival after ischaemic stroke. 41 Our current results should therefore be interpreted with caution, considering the size of the study. A further limiting factor might have been measuring the total adiponectin pool and not its subfractions.…”
mentioning
confidence: 78%
“…Moreover, the effect of adiponectin was supported by human cohort study in which hypoadiponectinemia apparently predicted the development of type 2 diabetes [7]. A low level of adiponectin was also associated with a higher risk for myocardial infarction and mortality after stroke [8].…”
Section: Introductionmentioning
confidence: 88%